Produção e obtenção de ciclodextrinas produzidas por CGTases bacterianas - Sanches, Raisa Déli de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The cyclomaltodextrin glucanotransferase ( EC 2.4.1.19 ) is an enzyme able to form cyclodextrin from starch . Cyclodextrins are cyclic oligosaccharides , which are the main types α - , β - and γ - CD which have 6, 7 and 8 glucose units connected by α - 1, 4 bonds. Two bacterial alkalophilic Bacillus sp subgroup alcalophilus E16 and Paenibacillus campinasensis H69 -3 was studied due to their good CGTase production, both of which were isolated from soil samples. The enzymatic activity was studied using the methods already pre-determined in previous studies, as dextrinizante, CD-phenolphthalein and protein determination. To achieve the purification and ultrafiltration processes were used for purification gel filtration resin Sephadex G-75. From these processes significant results were obtained for the purified extract produced by Bacillus sp subgroup alcalophilus E16 gave a purification factor of 35.4 times, a yield of 34.1% and a specific activity of 13.10 U / mg , while the purified extract of Paenibacillus campinasensis H69-3 resulted in a purification factor of 94.5 times , a yield of 33.2 % and specific activity of 23.64 U / mg . Tests were made for the production of cyclodextrins using concentrated crude extract by ultrafiltration CGTase produced by Paenibacillus campinasensis H69 3, hydrolysis of starches from different profile than 1.0 % , the enzyme acted converting starch into β- CD best in rice starch and tapioca , whereas a concentration of 2.5 % and better conversion is given cassava and corn starch . As for dextrinizing the starch, the concentrations of 1.0% and 2.5% showed the same profile hydrolysis , and cassava starches , potato and soluble showed better conversion, when compared to starches of rice and corn. Dextrinisation of starch was more effective at 1.0% concentration , because practically all starch was hydrolyzed at a concentration of 2.5% was slower hydrolysis , for 24 hours, the starches in the study were ...

A ciclomaltodextrina glucanotransferase (EC 2.4.1.19) é uma enzima capaz de formar ciclodextrinas a partir do amido. As ciclodextrinas são oligossacarídeos cíclicos, os quais os principais tipos são α-, β- e γ-CD, que apresentam 6, 7 e 8 unidades de glicose interligadas por ligações α-1,4. Duas bactérias alcalofílicas Bacillus sp subgrupo alcalophilus E16 e Paenibacillus campinasensis H69-3 foram estudadas por apresentarem boa produção de CGTase, ambas foram isoladas de amostras de solo. A atividade enzimática foi estudada utilizando os métodos já pré-determinados em estudos anteriores, como dextrinizante, CD-fenolftaleína e determinação de proteína. Para alcançar a purificação foram utilizados os processos de ultrafiltração e purificação por gel filtração em resina Sephadex G-75. A partir desses processos obteve-se resultados significativos, para o extrato purificado produzido por Bacillus sp subgrupo alcalophilus E16, obteve-se um fator de purificação de 35,4 vezes, um rendimento de 34.1 % e atividade específica de 13.10 U/mg, enquanto o extrato purificado de Paenibacillus campinasensis H69-3 resultou em um fator de purificação de 94.5 vezes, um rendimento de 33.2 % e a atividade específica de 23.64 U/mg. Foram feitos ensaios quanto a produção de ciclodextrinas utilizando o extrato bruto concentrado da CGTase por ultrafiltração produzida por Paenibacillus campinasensis H69-3, no perfil de hidrólise de diferentes amidos a 1.0%, a enzima atuou convertendo o amido em β-CD de melhor forma nos amidos de arroz e de mandioca, enquanto que na concentração de 2.5 % a melhor conversão se deu nos amidos de milho e mandioca. Quanto à dextrinização dos amidos, as concentrações de 1.0 % e 2.5 % apresentaram o mesmo perfil de hidrólise, sendo os amidos de mandioca, solúvel e batata apresentaram melhor conversão, quando comparadas aos amidos de arroz e milho. A dextrinização do amido foi mais efetiva na ...
Keywords: Tecnologia de alimentos; Enzimas - Aplicações industriais; Ciclodextrinas; Amido; Microorganismos alcalofílicos; Secagem em spray; Enzymes - Industrial applications